2018
DOI: 10.1103/physreva.97.012512
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-ring-down Doppler-broadening primary thermometry

Abstract: A step forward in Doppler-broadening thermometry is demonstrated using a comb-assisted cavity-ring-down spectroscopic approach applied to an isolated near-infrared line of carbon dioxide at thermodynamic equilibrium. Specifically, the line-shape of the P e (12) line of the (30012) ← (00001) band of CO 2 at 1.578 µm is accurately measured and its Doppler width extracted from a refined multispectrum fitting procedure accounting for the speed dependence of the relaxation rates, which were found to play a role eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…This accuracy makes LRT comparable even with the most precise PTs as those based in AGT. Even more, if compared with the other optical-based thermometry, the DBT [38], an accuracy improvement of a factor of 15 for T;300 K is prospected. Discrepancies under mK level of T-T 90 in 9-700 K range can be tested by this accurate LRT thermometry, and in particular, the T range of meteorological interest [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This accuracy makes LRT comparable even with the most precise PTs as those based in AGT. Even more, if compared with the other optical-based thermometry, the DBT [38], an accuracy improvement of a factor of 15 for T;300 K is prospected. Discrepancies under mK level of T-T 90 in 9-700 K range can be tested by this accurate LRT thermometry, and in particular, the T range of meteorological interest [27].…”
Section: Discussionmentioning
confidence: 99%
“…Freezing points of CO, CO 2 and H 2 O are also indicated. 5 A constant relative uncertainty of about 9ppm was considered in all the range of applicability corresponding to that reported for CO 2 at 300 K [38]. Different values could be achieved with different sample gases at other T's.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, large systematic deviations (of about 800 ppm) remained, mostly ascribed to weak hidden lines overlapping with the selected transition. Very recently, a comb-assisted highly sensitive CRDS spectrometer, operating at 1.578 m, has been developed [671] using pure CO 2 as a molecular gas target since, as discussed in [162], this molecule turns out to be an excellent choice for DBT measurements. It was subsequently shown that the combination of high sensitivity, absolute frequency calibration and extremely dense sampling of the absorption profiles leads to a statistical uncertainty of 8 ppm over a measurement time of only 5 h. Thermodymanic temperature determinations have been demonstrated by using this approach, with the spectroscopically unprecedented combined uncertainty of 14 ppm [671].…”
Section: Metrology 521 Doppler Thermometrymentioning
confidence: 99%
“…Optical frequency combs (OFCs) [1][2][3][4] enable increasingly precise applications of atomic and molecular spectroscopy [5], including primary thermometry [6,7], optical radiocarbon dating [8], sub-Doppler and Doppler-free spectroscopy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], ultrafast and multidimensional spectroscopy [27][28][29][30], survey spectroscopy of molecular ions and cold molecules [31][32][33], and time-resolved spectroscopy for fundamental chemical kinetics [34][35][36][37]. Applied spectroscopies [38] also make novel use of optical frequency combs for actively monitoring greenhouse gas fluxes [39][40][41], methane for open-path detection [42] and unambiguous source attribution [43] and reactive atmospheric species [44], elucidating the chemical composition of combustion and open flames…”
Section: Introductionmentioning
confidence: 99%